Manajemen Konflik dalam Pengembangan Wisata Desa Cibitung Wetan, Kecamatan Pamijahan, Kabupaten Bogor - Kurniati, Nia; P Lubis, Djuara; A Kinseng, Rilus (Sodality: Jurnal Sosiologi Pedesaan, 2021)
As a community develops, conflicts are inevitable. This case also applies to the Curug Cikuluwung tourism community. This research aims to analyze the conflicts, and how to manage the conflicts. This study used a qualitative approach with a case study method. The results of the study indicate that there are two conflicts that have occurred in the tourism development of Curug Cikuluwung village, namely, the first is a conflict between BUMDes and residents from a neighboring village (Pamijahan Village), the second is a conflict between the core manager of Curug Cikuluwung village tourism and the Cibitung Wetan village government. The first conflict has already had a solution, but the second conflict has no solution yet. The community has practiced community-based conflict management but it has not yet become a solution. Therefore, there is a need for mediation from parties who have authority over village tourism to mediate the conflict parties from the Pamijahan District Government, the Bogor Tourism Office, Bogor Village Community Empowerment office, and or Indonesia Power Company.